Gaya Komunikasi Parenting Ibu Milenials - Taufan Yoga Arifianto; Remia Putri Wulandari; Aldo Nopembia Adam (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Parenting is the attitude and behavior of parents in fostering the survival of a child in growth, development, and providing overall child protection both physically, socially, and mentally, as well as spiritual personality. The millennial mother's communication style is very important to express as digital literacy and evaluation and knowledge. The purpose of this study was to determine parenting communication styles for millennial mothers. The research method uses a qualitative approach. Data collection techniques used are interviews and literature review. Meanwhile, the analysis technique used is data collection, data reduction, describing, and concluding. The results of the study revealed that the communication style of millennial mothers has several parenting communication styles. These communication styles can be described as including: The Equalitarian Style; The Relinguishing Style; and The Controlling Style.